INCIDENCE OF PHARMACORESISTANT EPILEPSY IN KRASNOYARSK REGION (according to neurological center of university hospital data) - N. A. Shnayder; M. S. Pilugina; D. V. Dmitrenko; E. N. Shmatova; S. A. Erikalova (Эпилепсия и пароксизмальные состояния, 2016)
The goal of this study was to evaluate the incidence of cases pharmacoresistant varying severity in different forms of epilepsy among residents of Krasnoyarsk and the Krasnoyarsk region. We also analyzed the electronic database of Neurological Centre of Epileptology, Neurogenetics and Brain Research at University Hospital in 2008-2010. Random sample from the database was 199 cases of epilepsy initially aimed by neurologists or advised on seizures which is a difficult to control (pharmacoresistant?). We have shown that number of true pharmacoresistant cases in the studied sample did not reach 1 / 3 of cases (53/199, 26.6%) after adjustment of therapy. Thus, a personalized approach to treatment of epilepsy at Neurological Centre of Epileptology, Neurogenetics and Brain Research was the way to reduce pharmacoresistant cases.